Antibacterial Activity Test of 70% Ethanol Extract of Kersen Leaves (Muntingia calabura L.) against Cutibacterium acnes - Un Lala, Willybrordus Dewanto; Regaletha, Tadeus A. L.; Purnasari, Cahyani; Jannah, Insani Fitrahulil (Jurnal Biologi Tropis, 2026)
Acne ranks among the most prevalent skin issues and is linked to infection by Cutibacterium acnes. The rising rates of antibiotic resistance seen in Cutibacterium acnes necessitate the exploration of alternative plant-based treatments with antibacterial properties. One such plant that has demonstrated these antibacterial effects is the kersen leaf (Muntingia calabura L.). This research aimed to evaluate the antibacterial effects of a 70% ethanol extract of kersen leaves (Muntingia calabura L.) on the proliferation of Cutibacterium acnes. The research employed a true experimental design featuring a posttest only control group. The treatment categories included a positive control using Clindamycin, a negative control with sterile aquadest, and varying concentrations of kersen leaf extract at 1%, 2%, 4%, 8%, and 12%, with each group replicated four times. Data were assessed using the One-Way ANOVA method. The findings of the antibacterial test indicated that the 70% ethanol extract of kersen leaves effectively inhibited the growth of Cutibacterium acnes. The One-Way ANOVA analysis produced a p-value of less than 0.0001, which is lower than α = 0.05, signifying a notable discrepancy in the average inhibition zone diameters across the treatment groups. Ethanol extract from kersen leaves (Muntingia calabura L.) exhibits antibacterial properties against Cutibacterium acnes growth.